2001
DOI: 10.1159/000049031
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Serum Prolactin in Patients with Advanced Multiple Myeloma

Abstract: Background and Objective: The role of prolactin in immunoregulation and normal hemopoiesis is well known. However, prolactin also seems to be involved in the pathomechanism of malignancies and autoimmune diseases. Elevated serum prolactin levels were reported in patients with malignant lymphoma, colon and breast carcinoma, systemic lupus erythematosus and rheumatoid arthritis. Recently we demonstrated prolactin immunostaining in bone marrow cells of patients with multiple myeloma. Design and Methods: Serum pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…In this regard, it has been demonstrated HPRL and PRL-immunostaining in bone marrow cells of patients with multiple myeloma. PRL-immunopositive bone marrow cells disappeared and serum PRL normalized after treatment (Gado et al 2001). This study suggests that B lymphocytes are the source of HPRL in multiple myeloma.…”
Section: Human Studiesmentioning
confidence: 58%
“…In this regard, it has been demonstrated HPRL and PRL-immunostaining in bone marrow cells of patients with multiple myeloma. PRL-immunopositive bone marrow cells disappeared and serum PRL normalized after treatment (Gado et al 2001). This study suggests that B lymphocytes are the source of HPRL in multiple myeloma.…”
Section: Human Studiesmentioning
confidence: 58%
“…In addition, human cell lines of B-lymphoblastoid cells (40) and NHL cells (41) produce PRL. Furthermore, elevated serum PRL levels have been observed in patients with acute myeloid leukemia (20) and in advanced multiple myeloma, where PRL concentrations increased during disease progression (21). If the increased risk of hematopoietic cancers observed in the hyperprolactinemia women is by chance or is to some extent due to a stimulatory effect of PRL remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of PRL in human prostate pathology is not clarified and epidemiological data on PRL and risk of prostate cancer is sparse (15,16). Furthermore, it has been suggested that locally produced PRL could play a role in tumor development in gynecological (17), colorectal (18), tongue (19), and hematopoietic cancer (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, intracytoplasmic PRL has been detected in U266 cells, a human MM cell line [8]. Moreover, MM patients with advanced disease exhibit mildly elevated serum PRL [9]. However, neoplastic plasma cells overexpressing and secreting PRL enough to cause a 100-fold elevation in serum PRL would be unprecedented.…”
Section: Discussionmentioning
confidence: 99%